Pengaruh PER, ROE, EVA, ukuran perusahaan, nilai tukar dan tingkat inflasi terhadap return saham - Hidaratri, Suci Maulida; Titisari, Kartika Hendra; Siddi, Purnama (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The basic thing within the investment decision process is knowing the link between the expected return and also the risk of an investment. The existence of information of the expected return analysis may be a necessary strategy in investing. The aim of this study is to check the effect of price earning ratio (PER), return on equity (ROE), economic value added (EVA), company size, exchange rate and inflation rate on stock returns. This research was conducted on hospitality, restaurant and tourism sub-sector companies listed on the IDX for the 2017-2019 period. The full of population consists of 35 companies with samples taken as many as 11 companies using purposive sampling techniques. The analysis technique used may be a multiple rectilinear regression analysis technique. Supported the test results, it absolutely was found that PER and EVA had a positive and significant effect on stock returns. ROE, company size and rate of inflation have a negative and insignificant effect on stock returns. The exchange rate has a positive and insignificant effect on stock returns. The results of this study provide guidelines for creating investment decisions associated with the amount of return within the kind of stock returns and might be a reference for other parties who want to conduct further research and similar research within the future.